The Contribution of Teachersâ Accountability in Implementation of Learning Toward Implementation of Entrepreneurship Values - Natuna, Daeng Ayub (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The role of teacher in learning process should be in the form inderecting in each lesson or each material both in class and outside of the class. Teachersâ accountability in implementation of entrepreneurship values in learning process are the main key to realize an entrepreneur. This research aimed to know the level of teachersâ accountability , the implementation of entrepreneurship values, and to know how much the contribution of teachersâ accountability in the implementation of learning toward implementation of entrepreneurship values. This research used survey method. The sample were 84 teachers. The data were collected by using questionaires. The data were analized by using descriptive statistics and inferential statistics. The research findings stated that the implementation level of entrepreneurship values was very high. The contribution of teachersâ accountability variable in implementation of learning was also very high. The research findings also stated, the contribution of teachersâ accountability in implementation of learning toward implementation of entrepreneurship values was high (89,10%).In conclusion, teachersâ accountability variable in implementation of learning can decided teachersâ capability in implementation of entrepreneurship values to their students in learning process.